(untitled) (Global Journal of Human-Social Science, 2025)
This dissertation explores the significant role of social media in shaping political discourse and public opinion with a specific focus on the relationship between social media engagement and political attitude shifts among users By employing a mixed-methods approach the research encompasses quantitative data gathered from surveys measuring social media usage political beliefs and sentiment analysis of user-generated content complemented by qualitative data from interviews and focus groups to capture the nuanced perspectives of participants regarding the impact of social media The findings reveal a complex interplay between social media interactions and changes in political attitudes indicating that increased engagement with political content on social media correlates with more polarized opinions Moreover this study highlights that users perceive social media as both a tool for political mobilization and a platform contributing to misinformation underscoring the dualedged nature of its influence The significance of these findings extends beyond political science particularly in the context of healthcare as they suggest that the mechanisms through which public opinion is shaped can also affect health communication and policy formation within the healthcare sector Consequently understanding the dynamics of social media is paramount for healthcare professionals and policymakers to effectively navigate the landscape of public perception enabling better strategies for health education and crisis communication This research contributes to a deeper comprehension of how social media can be leveraged to foster informed public discourse thus emphasizing its potential implications for improving healthcare delivery and public health outcomes